The Role of Indonesia’s Islamic Philanthropic Institutions in Poverty Alleviation During the Covid 19 Pandemic 2022 - Rizkya Lutfi Amalin; Romli SA; Maftukhatusolikhah (Yayasan Ilomata, 2023)
The Covid-19 pandemic has had a tremendous impact on both health and the economy. One of the impacts is the increase in poverty in Indonesia where lot of people struggle for their daily needs. As one of the countries with the largest Muslim population in the world, Indonesia has a number of philanthropic institutions to enhance the welfare of society, one of which is BAZNAS. Through BAZNAS, it is hoped that cooperation with the government, the community, and other zakat management bodies to manage zakat nationally, to alleviate poverty and to improve people's welfare can be implemented. This is a qualitative research with a case study type. A case study research describes the current state of the research object based on facts and sober data. Zakat management is carried out according to their duties and responsibilities as stipulated in Zakat Management Law No. 23 of 2011. BAZNAS' efforts in eradicating poverty through zakat have been considered successful. Poverty alleviation carried out by BAZNAS RI contributed to 17.77% to the poverty alleviation of the national zakat program. In addition, this result contributes 0.31% to national poverty alleviation based on BPS.